Tajdidun Nikah Sebagai Resolusi Konflik Rumah Tangga Perspektif Maqāṣid As-Syarī’ah (Al-Hukkam: Journal of Islamic Family Law, 2025)
One emerging practice in Muslim communities is tajdidun nikah, which, although not explicitly regulated in classical Islamic law, can be examined through the framework of Maqāṣid as-syarī‘ah, emphasizing human welfare as the core objective of Islamic law. This study analyzes tajdidun nikah using the three levels of maqāṣid: daruriyyah (essential), hajiyyah (supportive), and tahsiniyyah (complementary). The findings indicate that tajdidun nikah is commonly motivated by marital conflicts involving elements of divorce and doubts regarding the validity of marriage. Although divorce pronounced outside the court is considered valid in Islamic law, state law based on Article 39 of Law No. 16 of 2019 continues to recognize the marriage in the absence of a court ruling. In practice, tajdidun nikah has proven effective in restoring marital harmony and strengthening spousal commitment, even when legal divorce procedures have not been completed. From the perspective of Maqāṣid as-syarī‘ah, tajdidun nikah falls within the category of hajiyyah benefits, as it serves as a secondary need that facilitates family life, prevents divorce, and reinforces marital stability. This practice reflects a cautious approach to resolving doubts and maintaining harmony, aligning with the sharia objective of safeguarding the five essential aspects of human welfare.
Keywords: Conflict Resolution, Maqāṣid As-Syarī'ah, Tajdidun Nikah